THU0371 HIGH INTENSITY EXERCISE HAS COMPARABLE 3-MONTH EFFECTIVENESS TO TNF-INHIBITORS ON DISEASE ACTIVITY IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. POST-HOC ANALYSES OF DATA FROM (THE ESPA TRIAL.). (2nd June 2020) - Aarrestad Provan, S.; Kristianslund, E.; Berg, I. J.; Solveig Dagfinrud, H.; Halvorsen Sveaas, S.
Abstract : Background: We have previously reported that a supervised 12-week high intensity cardiorespiratory and strengthening exercise programme reduced disease activity in patients with axial spondyloarthritis (axSpA), in an assessor blinded randomized controlled trial (ESpA)(1). There were no reports of disease flare, and the programme was deemed safe. It is of interest to compare the treatment response of the programme vs. the response to treatment with a biologic immune-modulating TNFalpha-inhibitor (TNFi). Objectives: To compare 3-month change in disease activity following an exercise programme vs. treatment with a TNFi, in patients with axSpA. Methods: Post-hoc comparison between participants in the intervention group in the ESpA and patients from NOR-DMARD, a longitudinal observational study, who commenced treatment with a TNFi (2).The inclusion criteria of ESpA were a diagnosis of axSpA, age 18-70 years and baseline BASDAI >3.5. Patients fulfilling these criteria were selected from NOR-DMARD. Data was collected at baseline and 3 months. The primary outcome was defined as ASDAS, and BASDAI scores, and secondary outcomes were BASDAI sub-scores and C-reactive protein (CRP). Baseline values were compared in bivariate analyses. Responses at 3 months were compared between the groups using ANCOVA models adjusted for age, gender and baseline values. The standardised mean difference in 3-month response between the exercise and TNFi groups was estimated by dividing the difference in change at 3-months by the standard deviation (SD) of change. Results: Fifty patients were randomised to the exercise intervention in the ESpA study, mean age (SD) 45.2 (0.6), 25 males (50%). 344 patients in the NORDMARD study were eligible for the current analyses, mean age (SD) 39.6 (1.5), 150 males (43.6 %). Baseline demographics and estimated marginal means for disease activity at - months are presented in table 1 . The standard mean differences are presented in Figure 1 . There were no significant differences in change in disease activity at 3-months between patients participating in ESpA and patients starting a TNFi. Conclusion: High intensity exercise has comparable 3-month effectiveness to TNF-inhibitors, in patients with axSpA. This confirms the important role of high-intensity exercise in the treatment of axSpA. References: [1]Sveaas SH et al. High intensity exercise for 3 months reduces disease activity in axial spondyloarthritis (axSpA): a multicentre randomised trial of 100 patients. Br J Sports Med. 2019. [2]Kvien TK et al. A Norwegian DMARD register: prescriptions of DMARDs and biological agents to patients with inflammatory rheumatic diseases. ClinExpRheumatol. 2005;23(5 Suppl 39):S188-S94. Disclosure of Interests: Sella Aarrestad Provan Consultant of: Novartis, Eirik kristianslund: None declared, Inger Jorid Berg: None declared, Hanne Solveig Dagfinrud: None declared, Silje Halvorsen Sveaas: None declared